First we have to use the definition for the curve y1 to find m1:
"y_1=3x^2-1\n\\\\ y'_1=\\cfrac{dy_1}{dx}=6x=m_1"
"x-3y=4\n\\\\ 1-3y'_2=0 \\implies y'_2=m_2=1\/3\n\\\\ \\text{For perpendicular lines we have}\n\\\\ m_1m_2=-1\n\\\\ \\implies m_1=-1\/m_2=-1\/(1\/3)=-3"
After we find m1 = -3, we can use the definition for y'1 to find the point (x*,y*) to find the equation of the tangent line:
"-3=m_1=6x \\implies x^*=-1\/2; y^*_1=3(1\/2)^2-1=-1\/4"
At last, we substitute to find the equation of the tangent line:
"y-y_1^*=m_1(x-x^*)\n\\\\ y-(-1\/4)=(-3)(x-(-1\/2))\n\\\\ y+(1\/4)=-3x-(3\/2)\n\\\\ y=-3x-\\cfrac{7}{4} \\implies 4y+12x+7=0"
Reference:
Comments
Leave a comment